Law and anthropology - Freeman, Michael D. A.; Napier, A. David (Oxford : Oxford University Press, 2009)
'Law and Anthropology' offers an insight into the state of law and anthropology scholarship today. Focusing on the inter-connections between the two disciplines it also includes case studies from around the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law and anthropology